THE PORTRAIT OF CONSERVATIVE INDONESIAN MUSLIM RELIGION IN THE MILLENNIAL ERA - Muhammad Andrean; Mardian Idris Harahap (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
The aim of this reaserch was to know the moderate values in Islam and straightening out people's perceptions of conservative Muslims. This research analyzes the interpretation of Shaikh Abdurrahman bin Nashir As-Sa'di in a verse that discusses religious moderation, and knows the reflection of its application to the Salafi Muslim community of Medan City. In this study, the author using the maudhui method in analyzing verses of the Qur'an, as well as used a qualitative-descriptive approach method by describing it in the form of words and language. The results showed that Islam does not invite its people to commit violence, extremes and exaggerations in religion. Salafi Muslims in Medan apply moderate values by prioritizing ukhrawi affairs but do not ignore worldly matters, respect differences, do not force opinions, but there is a bias in behavior in society.